Prevalence of Diabetic Retinopathy (DR) and its associated factors among diabetes patients in Primary Care Clinics, Kuantan, Pahang - Md Aris, Mohd Aznan; Mohd. Kamal, Khairidzan; Mohd Rus, Razman; Abdullah, Fa’iza (International Islamic University Malaysia, 2018)
Introduction: Diabetic retinopathy (DR) is one of the commonest complications of diabetes mellitus. This study was to determine the prevalence of diabetic retinopathy and its association with chronic kidney disease (CKD), high HbA1c and dyslipidemia among diabetic patients in government primary care clinics. Methods: A cross sectional study was carried out. The respondents were selected from diabetic registry at two government primary care clinics in Kuantan, Pahang via stratified random sampling method during the study period from May 2010 to April 2011. The respondents were interviewed and assessed clinically using a structured questionnaire. Retinal examination was performed by accredited staff using non-mydratic retinal imaging and DR was classified according to the International Clinical Diabetic Retinopathy Disease Severity Scale. Results: Out of 400 respondents, 58.8% diagnosed diabetes less than 5 years and 51.0% had uncontrolled blood pressure (>130/80 mmHg). The prevalence of diabetic retinopathy and maculopathy were 33.5% and of 17.8% respectively. Most of these patients (22.3%) had mild non-proliferative diabetic retinopathy. DR-patients had higher percentages of chronic kidneys disease (17.9% vs. 6.8%; p<0.001) and a higher mean of HbA1C (8.69 vs. 8.11; p=0.015)compared to non-DR patients. The study revealed that DR was independently associated with chronic kidney disease {OR: 3.46, 95% CI (1.76, 6.80)} and high HbA1c {OR: 1.12, 95% CI (1.02, 1.23)}. Those with dyslipidemia however, has 39% less risk of diabetic retinopathy {OR: 0.61, 95% CI (0.39, 0.94)}. Conclusion: This study shows that diabetic patients with CKD and high HbA1c have greater risks to develop diabetic retinopathy but has protective risk with dyslipidemia.